Multilocus sequence typing and genomic characterization of the novel Streptomyces strain SCPE-10, that resists 2,4-D toxicity and has bioremediation potential - Nildo Alfredo Nhampossa; João Victor Castro de Almeida Araújo; Vicente Almeida Serafim da Silva; João Ricardo Vidal Amaral; Cinara Souza da Conceição; Carlos Alberto Xavier Gonçalves; Eamim Daidrê Squizani; Sheila da Silva; Marcia Soares Vidal; Yinglong Chen; Andrew Macrae; Rodrigo Pires do Nascimento (Brazilian Journal of Microbiology, 2026)
The widespread use of aromatic herbicides such as 2,4-dichlorophenoxyacetic acid (2,4-D) has led to persistent environmental contamination, requiring efficient and sustainable biodegradation strategies. In this study, we isolated and characterized a novel actinobacterial strain, Streptomyces sp. SCPE-10, from contaminated coastal soil, capable of using 2,4-D as its sole carbon source. Phenotypic assays revealed robust growth on aromatic substrates, while whole-genome sequencing (Submission no. SUB15461668 ) followed by multilocus sequence analysis (16 S rRNA, recA, rpoB, atpD, gyrB, and trpB) revealed that SCPE-10 is closely related to Streptomyces phaeoluteichromatogenes . Functional genome annotation revealed a high abundance of genes involved in aromatic compound degradation, including cytochrome P450 monooxygenases, ring-cleaving dioxygenases, and dehalogenases. KEGG and antiSMASH analyses identified multiple metabolic pathways and 28 biosynthetic gene clusters (BGCs), including clusters for polyketides, nonribosomal peptides, terpenes, siderophores, and ectoine. Notably, SCPE-10 harbors key genes related to the degradation of benzoate, naphthalene, toluene, xylene, and 2,4-D, indicating broad-spectrum catabolic potential. These findings suggest that Streptomyces sp. SCPE-10 is a promising candidate for the bioremediation of herbicide-contaminated environments and the exploration of novel secondary metabolites.